The Potential Development of Conciliator in Community Justice: The Case Study of Chompoo Community Justice Center, Saraphi District, Chiang Mai Province - ตรัยตรึงตรีคูณ, จรินทิพย์ (Community and Social Development Journal, 2018)
This objective of this research is, to study the problems and the barriers in the potential of community justice conciliators in community justice center and development the potential of community justice conciliators in community justice center, Chompoo sub-district, Saraphi district, Chiang Mai province. In order that, this research is quality of research methodology to be a tool for analyzing, in other words, at first part by collecting information as documentary and the other part from interview people, and meeting the leader group of community, community conciliators, included the test from practice conciliation. By using the framework concept of developing community justice system from the Ministry of Justice that conciliation or conflict management has held to be the main significant mission to run the process of community justice center to be effective. The results of this research has found, 1) The conciliators at community justice center in sub-district does not prescribe the specific of qualification on the framework of setting and management community justice center that shall be apply to The Principle of Local Administrative Act B.E. 2457 and The Principle of Ministry of Interior in Practice to Conciliation By the Village Committee B.E. 2530 that prescribed to be a duty of villager committee to take conciliation that occurs to the village in civil case and minor offense in criminal case. 2) The potential of conciliators at community justice center in Chompoo sub-district, Saraphi district, Chiang Mai, should get the potential development of conciliators on knowledge of law included the process of conciliation in practice for duty for serve justice to people in community to be more effectiveness. Nevertheless, it is found out that the community justice center is lack from the format of administration management process for serve justice especially on the conciliation for people in community according to the framework at developing community justice from Ministry of Justice.